2017
DOI: 10.18400/tekderg.334196
|View full text |Cite
|
Sign up to set email alerts
|

Farklı Tip Betonarme Binalar İçin Geliştirilmiş Hasar Tahmin Yöntemleri

Abstract: ÖZBu çalışmanın başlıca amacı; olası bir depremde meydana gelecek hasar ve kayıp olasılıklarını tahmin etmeye yarayan bir hasar tahmin metodu geliştirmektir. Bu amaçla; 11 farklı tip betonarme yapı için hasar olasılık grafikleri elde edilmiştir. Çalışma kapsamında 341 adet betonarme konut binası; yapım yılı, kat adedi ve bina kalitesi gibi ortak özelliklerine göre gruplanmıştır. Toplam 11 farklı bina grubu elde edilmiştir. Binaların tamamı bilgisayar ortamında 3 boyutlu olarak modellenmiş ve her bir bina model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…As a result, it is observed that the application of carbon fiber reinforced polymer wrapping improves the current performance. Various methods are suggested to predict the actual behavior of a structural system [21][22][23]. Studies show that the performance of carbon fiber reinforced polymer confined concrete and reinforced concrete elements can be predicted through finite element analysis [24].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, it is observed that the application of carbon fiber reinforced polymer wrapping improves the current performance. Various methods are suggested to predict the actual behavior of a structural system [21][22][23]. Studies show that the performance of carbon fiber reinforced polymer confined concrete and reinforced concrete elements can be predicted through finite element analysis [24].…”
Section: Introductionmentioning
confidence: 99%
“…As earthquake disasters have become more frequent in recent years and are responsible for direct and indirect losses, an in-depth understanding of earthquakes is required [1]. Before and after earthquakes, it is essential to maintain the transportation and safety of bridges.…”
Section: Introductionmentioning
confidence: 99%
“…Böylelikle, hızlı değerlendirme sonuçları ile deprem geçirmiş yapıların gerçek davranışı arasındaki tutarlılığı da ortaya koymaya çalışmışlar, inceledikleri binaların %5'ini çok tehlikeli ve %47'sini yüksek öncelikli olarak sınıflandırmışlardır. [12] muhtemel bir depremde oluşabilecek hasar ve kayıp ihtimallerini tahmin etmek için bir metot geliştirmeye çalışmışlar, bu amaçla 11 farklı tipteki betonarme yapının doğrusal olmayan statik itme analizlerini yapmışlardır. Araştırmacılar tarafından, analiz sonuçlarına bağlı olarak her bina grubuna ait 4 farklı hasar ihtimalini gösteren "kırılganlık eğrileri" oluşturulmuştur.…”
Section: Introductionunclassified